1997
DOI: 10.1097/00000372-199702000-00007
|View full text |Cite
|
Sign up to set email alerts
|

Epithelial Induction in Dermatofibroma: A Role for the Epidermal Growth Factor (EGF) Receptor

Abstract: Dermatofibroma (DF) refers to a spectrum of firm, nodular, nonencapsulated lesions that occur commonly on the extremities. Histologically, DF is composed of spindle cells with variable differentiation toward histiocytic and vascular elements, often associated with epithelial hyperplasia and basilar keratinocyte pigmentation that histologically may simulate basal cell carcinoma (BCC). The characteristic epithelial changes are likely to be mesenchyma-mediated and probably represent a host reparative response oth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
30
0
2

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(32 citation statements)
references
References 11 publications
0
30
0
2
Order By: Relevance
“…It is believed that these epithelial changes are likely to be mesenchyme mediated, possibly related to epidermal growth factor receptor. 10 It may be possible that surgical or nonsurgical scarring can induce a distinctive subepidermal plate-like proliferation, similar to that present in the solitary or multiple variant of TFI.…”
Section: Discussionmentioning
confidence: 99%
“…It is believed that these epithelial changes are likely to be mesenchyme mediated, possibly related to epidermal growth factor receptor. 10 It may be possible that surgical or nonsurgical scarring can induce a distinctive subepidermal plate-like proliferation, similar to that present in the solitary or multiple variant of TFI.…”
Section: Discussionmentioning
confidence: 99%
“…Dermatofibromas, including the variants, may be associated with acanthosis or hyperplasia of the overlying epidermis and hyperpigmentation of the basal layer 22 . It has been suggested that epidermal growth factor may play a role in the pathogenesis of the epidermal hyperplasia 23 .…”
Section: Discussionmentioning
confidence: 99%
“…17 -19 These epithelial changes probably stem from mediators released by the neoplastic fibroblasts interacting with nearby keratinocytes. 20,21 A superficial dermal grenz zone or deep lymphoid nodules may be present in some cases. 22,23 Mitoses in classic examples of DF are uncommon, but mitotic figures can be frequent in cellular and aneurysmal variants.…”
mentioning
confidence: 99%